Vers une prise de conscience de la dégradation des écosystèmes marins guadeloupéens - Anne-Laure Transler; Pascal Saffache; Didier Moullet (Études Caribéennes)
Ecosystem management of the islands of Guadeloupe, like that of the ecosystem of the Grand Cul-de-Sac Marin, is limited by the administrative boundaries that constrain the scope of some of the policy, management or protection initiatives. Cooperation between the various administrative divisions needs to be encouraged. Efforts are being made in this regard on a inter municipality scale with the elaboration of river development plan of “Grand Rivière” (Goyaves Commune) with the collaboration of the Community of Commons Northern Basse-Terre. This inter municipality cooperation will be able to define a new framework for a planning policy among municipalities within a functional area.